2018
DOI: 10.1111/jocs.13709
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm formation after valve sparing root replacement in children with Loeys-Dietz syndrome

Abstract: Pseudoaneurysms following aortic root replacement with VSRR can occur in children with severe subtypes of LDS. Long-term surveillance is required to detect these potentially life-threatening lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…A retrospective study by Liu et al found that 4 of 31 patients that developed postoperative pseudoaneurysms requiring reoperation. They concluded that pseudoaneurysms following aortic root replacement can occur in patients with severe subtypes of LDS as all of their patients had a severe subtype with a TGFBR2 mutation [10]. This was also the case with our patient.…”
Section: Discussionsupporting
confidence: 75%
“…A retrospective study by Liu et al found that 4 of 31 patients that developed postoperative pseudoaneurysms requiring reoperation. They concluded that pseudoaneurysms following aortic root replacement can occur in patients with severe subtypes of LDS as all of their patients had a severe subtype with a TGFBR2 mutation [10]. This was also the case with our patient.…”
Section: Discussionsupporting
confidence: 75%
“…Risks associated with the prostheses have led to the development of valve-sparing aortic root replacement (VSRR). VSRR eliminates the need for long-term anticoagulation therapy and subsequent surgeries to replace worn out prosthetic valves [83]. Recent studies on short-and mid-term outcomes of VSRR have shown superiority over traditional valve replacements in terms of survival and need for reoperation [84].…”
Section: Loeys-dietz Syndromementioning
confidence: 99%
“…Unfortunately, there is significantly increased likelihood of pseudoaneurysms in young children following VSRR; thus, further long-term studies are needed to define the optimal surgical management strategy. In addition, ongoing surveillance imaging with CTA or MRA is warranted post operatively as well [83].…”
Section: Loeys-dietz Syndromementioning
confidence: 99%
“…Aortic pseudoaneurysms may occur following the replacement of the ascending aorta and arch in patients with connective tissue, congenital, or atherosclerotic disease . Patients with Takayasu's arteritis may also develop pseudoaneurysms due to calcification of aortic tissue .…”
mentioning
confidence: 99%
“…
Aortic pseudoaneurysms may occur following the replacement of the ascending aorta and arch in patients with connective tissue, congenital, or atherosclerotic disease. [1][2][3] Patients with Takayasu's arteritis may also develop pseudoaneurysms due to calcification of aortic tissue. 4 We present images of a patient with Takayasu's arteritis who developed a giant pseudoaneurysm compressing the right coronary artery (RCA) following aortic arch replacement.
…”
mentioning
confidence: 99%